1998
DOI: 10.1021/ma9718255
|View full text |Cite
|
Sign up to set email alerts
|

Cure Reaction Pathways of Bismaleimide Polymers:  A Solid-State 15N NMR Investigation

Abstract: The cure reaction pathways of a bismaleimide resin with a diamine are investigated using solid-state 15 N NMR spectroscopic techniques with specifically labeled monomers. These techniques provide clear identification of at least three different reaction pathways in the curing resin, one of which has previously been only postulated. In the homopolymerized bismaleimide resin system, maleimide ring addition has previously been shown to be the only observable reaction. When co-reacted with an amine, Michael additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…For similar reasons we also recently showed that a combination of different cure kinetic models was required to accurately represent a similar modified BMI system. 32 This article reports on our investigation relating the glass-transition temperature and conversion for a BMI system consisting of three main components: BMI (4,4Ј-methylenebis-[maleimidobenzene]), DABPA (2,2Ј-diallylbisphenol A), and 4,4Ј-diaminodiphenylsulfone (DDS). The major reaction types occurring in this type of system containing diallybisphenol have been proposed in the literature 33,34 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For similar reasons we also recently showed that a combination of different cure kinetic models was required to accurately represent a similar modified BMI system. 32 This article reports on our investigation relating the glass-transition temperature and conversion for a BMI system consisting of three main components: BMI (4,4Ј-methylenebis-[maleimidobenzene]), DABPA (2,2Ј-diallylbisphenol A), and 4,4Ј-diaminodiphenylsulfone (DDS). The major reaction types occurring in this type of system containing diallybisphenol have been proposed in the literature 33,34 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…2 For example, the moisture absorption rate of CEs is lower than that of epoxy, polyimide and BMI resins. 3,4 Cyanate esters are studied as precursors to carbon-carbon materials because they may be cured without outgassing and they form dense, thermally stable resins. 5 Carbon-carbon composite materials are formed by impregnating continuous carbon fiber cloths or performed with an organic thermoset resin (usually phenolic resins), curing the resin, then followed by high temperature pyrolysis to carbonize the matrix resin.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in Refs. [23][24][25][26][27][28][29][30], polyaspartimides, which could be obtained through Michael addition reaction between amine and maleimide compounds, have shown more favorable properties in processing than do the condensation type polyimides.…”
Section: Introductionmentioning
confidence: 99%